HDAC inhibitors enhance the anti-tumor effect of immunotherapies in hepatocellular carcinoma - Shen, Chen; Li, Mei; Duan, Yujuan; Jiang, Xin; Hou, Xiaoming; Xue, Fulai; Zhang, Yinan; Luo, Yao (Frontiers in Immunology, 2023)
Hepatocellular carcinoma (HCC), the most common liver malignancy with a poor prognosis and increasing incidence, remains a serious health problem worldwide. Immunotherapy has been described as one of the ideal ways to treat HCC and is transforming patient management. However, the occurrence of immunotherapy resistance still prevents some patients from benefiting from current immunotherapies. Recent studies have shown that histone deacetylase inhibitors (HDACis) can enhance the efficacy of immunotherapy in a variety of tumors, including HCC. In this review, we present current knowledge and recent advances in immunotherapy-based and HDACi-based therapies for HCC. We highlight the fundamental dynamics of synergies between immunotherapy and HDACi, further detailing current efforts to translate this knowledge into clinical benefits. In addition, we explored the possibility of nano-based drug delivery system (NDDS) as a novel strategy to enhance HCC treatment.